Evaluation of Breakfast Cereals Produced from Finger Millet, Wheat, Soybean, and Peanut Blends - Idris, Kaida Zubairu; Mansir, Abba; Ahmad, Tijjani (International Journal of Food Sciences, 2019)
Purpose: The study sought to evaluate breakfast cereals produced from finger millet, wheat, soybean, and peanut blends Methodology: In this study, finger millet based breakfast food analysis was conducted, with supplementation of wheat, soybean, and peanut in the ratios of (100:0), (90:10), (80:20), (70:30), and (60:40). These products were analyzed for proximate composition, mineral contents, and sensory attributes using AOAC 2O10, AAS flaming, and method described by Adenguwa et,al., (2014) respectively. Results: The results for the proximate composition ranged from 61.70 to 71.25 %, 6.95 to 7.85 %, 2.40% to 3.20%, 9.70 % to 13.5 %, 1.5% to 8.50%, and 2.13 % to 4.10 % for carbohydrate, moisture, ash, protein, fat, and fibre respectively. There was significant increase in the protein, fat, fiber, and energy contents, and decrease in only carbohydrate contents at (p<0.05) with increase in supplementation. There were general increase contents of Zn, Na, and K with equal decrease in the Ca contents in all the samples A -E at (p<0.05). The mineral composition of this food is good for its efficacy to alleviate some level of macro-minerals deficiencies. The scores for taste ranged between 7.20 - 7.50, the scores range for aroma was from 6.60 - 6.90, and 6.23 - 7.10 was the score range for mouth feel, the general acceptability which has a score range of 6.67 - 7.47 in samples A to E. There was significant difference (p<0.05) across the samples in all the sensory qualities. Unique contribution to theory, practice and policy: This shows that this breakfast cereal product will be accepted by the consumers when expose to the market due to its characteristic organoleptic sensory appeal. It was recapitulated that this product should be adopted for better nourishment and huger quenching due to lots of condensed nutrients of significant amount